Pengabaian Saksi Verbalism Oleh Judex Factie Sebagai Alasan Pengajuan Kasasi Terhadap Putusan Bebas Dalam Putusan Mahkamah Agung Nomor 2627 K/Pid.Sus/2010 - Utami, Mutiara Resky (Sebelas Maret University, 2013)
This research aims are to find out whether the verbalism witness overlooking by judex factie in evidence examination as justification for the public prosecutor in filing appeal to the supreme court in verdict of freedom in drugs case has met the penal procedural law as well as to find out the construction of the Supreme Court’s Judge in assessing the reason of public prosecutor’s appeal to the Supreme Court. This is a normative legal research using primary and secondary law materials. Technique of collecting data used was library study to collect the material law by means of reading legislations, official documents and literatures relevant to the problem studied. Technique of analyzing data used was deductive logic technique.The result of research showed that firstly, the reason of appeal to Supreme Court the Public Prosecutor filed had not met the provision of Article 253 clause (1) of Code of Criminal Procedure because the reason used was that beyond the juridical provision, namely the result of authentication. Secondly, the legal construction of the Supreme Court’s judge in investigating the case was corresponding to the provision because the appeal to the Supreme Court was filed against the verdict of freedom. Keywords: Verbalism Witness, Justification, Psychotropics.